2021
DOI: 10.3390/coatings11111292
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Synthetic Cilia and Arrhenius Energy on Double Diffusive Stream of Radiated Hybrid Nanofluid in Microfluidic Pump under Ohmic Heating: An Entropic Analysis

Abstract: This study investigates the thermal aspects of magnetohydrodynamic double diffusive flow of a radiated Cu-CuO/Casson hybrid nano-liquid through a microfluidic pump in the presence of electroosmosis effects. Shared effects of the Arrhenius activation energy and the Joule heating on the intended liquid transport are also incorporated. The inner wall of the pump is covered with electrically charged fabricated cilia mat that facilitates flow actuation and micro-mixing process. The governing equations for the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Illustrates the computational effects of DD-convection on a stretched sheet. In [53][54][55][56][57][58] , some pertinent double diffusion studies for peristaltic movement is given.…”
Section: Thermal Expansion Grashof Number G Rcmentioning
confidence: 99%
See 1 more Smart Citation
“…Illustrates the computational effects of DD-convection on a stretched sheet. In [53][54][55][56][57][58] , some pertinent double diffusion studies for peristaltic movement is given.…”
Section: Thermal Expansion Grashof Number G Rcmentioning
confidence: 99%
“…(iv) Equations for the volume fractions of nanoparticles, the concentration of solute, and heat energy The heat energy, concentration of solute, and nanoparticle volume fraction [53][54][55][56][57][58] : are calculated utilizing Oberbeck-Boussinesq hypothesis as follows:…”
Section: Basic Equations (I) Maxwell's Equationmentioning
confidence: 99%
“…Recently, Saleem et al [ 128 ] numerically analyzed the transportation of thermally radiated nanofluid in the microchannel in which the inside layer was settled with artificial cilia. In similar physical conditions, parameters such as electric potential, directional flow, velocity, pressure, temperature, and entropy generation were numerically analyzed by the same group [ 129 , 130 , 131 ]. Outside osmotic pumps, a numerical study [ 132 ] was reported to examine the heat transfer in the rectangular channel under the influence of the mechanical stirrer or artificial cilia.…”
Section: Artificial Cilia For Microfluidic Applicationsmentioning
confidence: 99%
“…To achieve the desired heat exchange rate, appropriate nanoparticle types with specific weight percent are employed. The hybrid nanofluids found large applications in different aspects of human life such as transportation [5], defense [6], microfluidics [7], etc. ; in this way, the concept of hybrid nanofluids has been the subject of numerous numerical and experimental investigations.…”
Section: Introductionmentioning
confidence: 99%